Monumental minnepolitikk: Russlands bruk av sovjetiske og russiske krigsminnesmerker i Nord-Norge 2014–2023 - Joakim Aalmen Markussen (Nordisk Østforum, 2024)
Abstract: Monumental Memory Politics: Russia’s Utilization of Soviet and Russian War Memorials in Northern Norway 2014–2023 This article explores how changes and developments of Kremlin’s WWII memory politics has impacted the use of Soviet and Russian war memorials by Russian diplomats in Northern Norway between 2014 and 2023. It examines the growing interest of Russia’s consulate general in Kirkenes in organizing joint commemorative events with local Norwegian politicians, notably on Russia’s Victory Day on May 9th. Since 2014, memory policy has increasingly become a constituent of security policy in Russia, and challenges to the official narrative of World War II are viewed as threats to national identity and integrity. How has Russia’s utilization of Soviet and Russian WWII memorials in Northern Norway changed between 2014–2023? This article demonstrates how the Consulate General has promoted the official Russian narrative of the Soviet Victory to memorials in Northern Norway and incorporated the use Russian military-patriotic symbols like St. George ribbons during its commemorations. Through its progressively assertive memory policy, the Consulate General has worked to inscribe Norway as an ally in Russia’s ongoing memory wars in Europe.